Anarchizm w „Homku” Ruchu Społeczeństwa Alternatywnego w kontekście mowy wrogości - Grzelka, Monika; Kula, Agnieszka (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2019)
This text analyses the Homek magazine published by Ruch Społeczeństwa Alternatywnego (RSA) [Alternative Society Movement] – a community of people with neoanarchist views first co-creating the underground Solidarność and later functioning independently. Homek, as an underground newspaper, was initially published bi-weekly, then monthly and later irregularly. This article focuses on, firstly, the RSA community’s position on hostile attitudes (including the so-called hate speech) and, secondly, on the use of the term walka [fight] as what we believe to have been a self-creation device.